2014
DOI: 10.1080/10720537.2013.849214
|View full text |Cite
|
Sign up to set email alerts
|

An Exemplary Life? A Personal Construct Analysis of the Autobiography of Rudolf Hoess, Commandant of Auschwitz

Abstract: This article analyses the autobiography of Rudolf Hoess, commandant of Auschwitz. Textual grid, ABC and self-characterisation analyses of the autobiography are used to construe Hoess's writing. The textual grid analysis suggests that Hoess saw his adult self as being different from others but his young self as similar to Jews. Conflicts in self-construing are identified. The ABC analysis indicates that, from his perspective, it made sense for Hoess to choose not to leave the concentration camp service. The sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
2
0
4
Order By: Relevance
“…(Post, Sprinzak, & Denny, 2003, p. 171). One such extremist person is Anders Breivik, who killed 77 people in the cause of countering "cultural Marxism" and "multiculturalism," and whose beliefs and actions were considered from a personal construct theory perspective by Winter and Tschudi (2015) in one of a series of attempts to apply a credulous approach to people who have engaged in extreme violence (Reed et al, 2014;Winter, 2006Winter, , 2007Winter, , 2016aWinter et al, 2007Winter et al, , 2016. Analysis of an interview conducted by Breivik with himself, similar to a self-characterization (a method developed by Kelly (1955) in which the individual writes an autobiographical character sketch in the third person), indicated that he had experienced numerous invalidations of his construing in his early life, but that the development of his radical beliefs allowed him to reconstrue himself as a "Perfect Knight" (Berwick, 2011(Berwick, , p. 1435).…”
mentioning
confidence: 99%
“…(Post, Sprinzak, & Denny, 2003, p. 171). One such extremist person is Anders Breivik, who killed 77 people in the cause of countering "cultural Marxism" and "multiculturalism," and whose beliefs and actions were considered from a personal construct theory perspective by Winter and Tschudi (2015) in one of a series of attempts to apply a credulous approach to people who have engaged in extreme violence (Reed et al, 2014;Winter, 2006Winter, , 2007Winter, , 2016aWinter et al, 2007Winter et al, , 2016. Analysis of an interview conducted by Breivik with himself, similar to a self-characterization (a method developed by Kelly (1955) in which the individual writes an autobiographical character sketch in the third person), indicated that he had experienced numerous invalidations of his construing in his early life, but that the development of his radical beliefs allowed him to reconstrue himself as a "Perfect Knight" (Berwick, 2011(Berwick, , p. 1435).…”
mentioning
confidence: 99%
“…Green (2016), R. A. Neimeyer et al (2003), Reed et al (2014), y Winter y Tschudi (2015). En el estudio de S. J.…”
Section: Estudios Empíricosunclassified
“…La terapia sirvió para que la cliente dejase de usar un patrón rígido en la anticipación de la experiencia. Los artículos de Reed et al (2014), Winter y Tschudi (2015) y Green (2016) analizan tres casos clínicos a través de sendas obras literarias. En su conjunto, exploraron de la evitación del sentimiento de culpa del comandante Hess (Reed et al, 2014); la ausencia de constructos que clasifican personas en la figura de Breivik (Winter y Tschudi, 2015); la evolución de las emociones de aislamiento e inferioridad hacia sentimientos de venganza y castigo hacia los demás en un asesino en serie (B.…”
Section: Estudios Empíricosunclassified
See 2 more Smart Citations